Motivation for Mobile Learning: Teacher Engagement and Built-In Mechanisms - Snezhko, Zoya; Babaskin, Dmitrii; Vanina, Ekaterina; Rogulin, Rodion; Egorova, Zhanna (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The relevance of the study of mobile learning as an upcoming trend in education in the context of the COVID-19 pandemic is not denied. The study of students’ ability and motivation to use modern technologies of mobile learning is characterized by novelty. However, the problematic issue of studying the motivation of students and teachers for mobile learning in today's pandemic remains relevant. The purpose of the study is to examine some aspects of the formation of students' motivation (intrinsic motivation: interest in the subject of study, understanding of its significance for further career; extrinsic motivation: points, awards, recognition), as well as the role of teachers in this process and the influence of cognitive abilities of a person on their motivation and academic achievement. The study is based on the method of experiment as well as the interviews and analysis of student reports. There were 185 students (19-22 years old) from Sechenov First Moscow State Medical University and Far Eastern Federal University participating in the study. After the participants had listened to an online lecture on the topic "Neuro-linguistic programming", they were asked to make a report on the topic of the same name and expand the information. Next, the students were interviewed. The results showed that 89% of students were interested in the issue and 69% noted a desire to learn more information on this topic; 100% of participants actively use mobile devices with Internet access for educational purposes and, in particular, for making the required report. However, only 12% of respondents believe that mobile learning alone can be used in order to study specialized disciplines at their university. Thus, 43% of students find it difficult to perceive information from the screen of a smartphone (tablet); 61% of students prefer traditional education to mobile learning, which is probably due to the novelty of this process; 65% of respondents noticed that their knowledge is deteriorating due to the use of mobile (distance) learning. In connection with the results obtained, the following recommendations were made to improve the educational process: to explain to students the importance and usefulness of the topic under study; to use adequate pedagogical methods in the context of mobile learning; to provide feedback and the ability to communicate to students during mobile learning; to take into account the personality and learning style of a student; to use all types of intrinsic and extrinsic motivation of students in accordance with specific circumstances. The most popular motivation factors for mobile learning are possibility of improving exam grades (65%), possibility of improving knowledge (25%), and broadening horizons and deep interest in the topic (10%). Developing applications that will take into account the needs of a particular university and specialty will also make a contribution. Teachers are also encouraged to use a play-based approach and a student reward system in order to increase the level of motivation (additional points, a simplified exam scheme, etc.). The practical significance and prospects for further research are presented by the opportunities of increasing students’ motivation in the context of mobile learning, and, consequently, the success of their studies. The results can be used in the comparative study of mobile learning possibilities in modern conditions and teachers’ involvement in it in different countries.